Slow oxidation of magnetite nanoparticles elucidates the limits of the Verwey transition - Taehun Kim (Nature Portfolio, 2021)
The Verwey transition in magnetite has been studied for nearly eight decades since its discovery in the 1940s. Here, Kim et al. elucidate the influence of chemical doping by extremely slow oxidization process with magnetite nanoparticles, revealing why first- and second-order regimes of the Verwey transition are observed.